Collection of microalgae and cyanobacteria Kazakh National University named after al-Farabi and prospects of its use (Experimental biology, 2016)
Currently, collection of microalgae and cyanobacteria Kazakh National University al-Farabi (CCMKazNU - Culture Collection of microalgae, Al-Faraby Kazakh National university) consists of 54 strains of 13 genera, 25 species. The basis of the collection fund is green microalgae Chlorella mainly relate to childbirth, of Dunaliella and Chlamydomonas as well as cyanobacteria is mainly represented by the genera of Spirulina, Nostos and Synechocystis. The collection contained strains isolated from soil and water algological samples collected on the territory of Kazakhstan and Mongolia, as well as obtained from other collections of Russian microalgae (CALU, IPPAS, PGC), Uzbekistan (Collection of Botany Institute of algae cultures) and collection Hlamidomonas Center Duke University USA. Also provides mutant strains of microalgae and cyanobacteria obtained by mutagenesis and selection. On the basis of the collection of microalgae research is carried out in areas of molecular-genetic taxonomy of selected microalgae and cyanobacteria, microalgae biology and ecology, physiology and biochemistry of algae. Main research areas are related to the search for promising crops phototrophic microorganisms with biotechnological importance, in particular for the production of biologically active substances (BAS) in medicine and dietary supplements (dietary supplements) in agriculture, biofuels, bio-fertilizers, conducting biomonitoring and bioremediation of disturbed environmental objects .
Keywords: collection; microalgae; cyanobacteria strains algological pure culture